Intracranial Hemorrhagic Complications in a Child with Tetralogy of Fallot: A Case Report - Mochammad Haikal Alhamdi; Naufal Dzulhijar; Agus Fitrianto (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Background: Tetralogy of Fallot?(ToF) is one of the cyanotic congenital heart diseases, accounting for roughly?7%–10% of all congenital heart?disease cases, with an equal male?to?female ratio and an incidence of 3?–?5 per?10?000 live births. Intracranial hemorrhagic complications in ToF are rare but can be life?threatening if not managed promptly. This report aims to offer practical recommendations for handling deteriorating ToF cases that lead to intracranial bleeding. Case Illustration: A six?year?old child presented with a four?hour history of reduced consciousness prior to hospital admission. Additional complaints included fever, cough, rhinitis, projectile vomiting, and seizures. Physical examination showed normal consciousness at admission, fever, and dyspnea. Imaging and ancillary tests revealed subdural and subarachnoid hemorrhages accompanied by elevated intracranial pressure. The patient had a known diagnosis of ToF and attended regular follow?ups. Management focused on lowering intracranial pressure and treating the infection. On subsequent follow?up visits, the symptoms subsided and the patient’s clinical condition gradually improved. Discussion: Congenital heart disease can promote intracardiac thrombus formation, giving rise to emboli in the peripheral circulation. Secondary erythrocytosis increases blood viscosity, while chronic hypoxemia activates neutrophils and mononuclear cells, leading to endothelial injury. Platelet–endothelial interactions further enhance intravascular thrombogenesis, collectively predisposing ToF patients to cerebrovascular events. Conclusion: Tetralogy of Fallot can cause mortality primarily through hypoxia, cerebrovascular complications, and brain abscesses. Cerebrovascular complications, including intracranial hemorrhage, arise through multifactorial mechanisms